Adverse childhood experiences and educational outcomes, problem drinking and the perpetration of violence - Pieterse, Duncan (School of Economics, 2025)
Violence in South Africa is very high by international standards. Many South African children experience adverse events, such as childhood maltreatment, that are a reflection of these high levels of violence. Due to a lack of data we know little about the extent, nature, causes and long-term consequences of adverse childhood experiences in South Africa. We contribute to closing this gap in the empirical literature by using the Cape Area Panel Study (which is the only representative dataset that includes a module on adverse childhood experiences for a metropolitan city in South Africa) to explore the extent and nature of adverse childhood experiences as well as the associated long-term developmental consequences. We supplement various waves of the Cape Area Panel Study with official crime statistics from the South African Police Service; demographic information from the 2001 Census; and spatial and demographic information from Cape Town. In our empirical chapters we explore the impact of childhood maltreatment and having a problem drinker in the home during childhood on the perpetration of violence, problem drinking and educational outcomes. We control for potential confounders using a range of statistical techniques (including neighbourhood fixed effects) and add several robustness checks (including household and sibling fixed effects) to evaluate the strength of our findings. Our results indicate that maltreated children suffer large adverse consequences in terms of their numeracy test scores and probability of dropout and the estimated effects of maltreatment are larger and more consistent for the most severe types of maltreatment. Children with a parent who is a problem drinker during childhood suffer adverse consequences in terms of childhood maltreatment and are at increased risk of problem drinking and the perpetration of assault against strangers later in life. Once we control for having a problem drinker in the home during childhood and binge drinking during adulthood, there is no evidence to support the cycle of violence hypothesis. Having problem drinker in the home during childhood doubles the probability of assaulting a stranger for black and coloured young adults. The strength of the effect of having a problem drinker in the home during childhood suggests the need for a more nuanced understanding of the childhood origins of violent behaviour in an environment where the prevalence of alcohol abuse is high.